Exploring farmers’ perspectives on agroforestry practices in Rangamati Hill tracts of Bangladesh - Setu Chakma; Mithun Kumar Ghosh; Md Mahbub Alam; Ajnabi Sultana; Eco Talukder; Netui Chakma (Penerbit Universiti Kebangsaan Malaysia, 2024)
Agroforestry has been a vital component of the livelihoods of hill communities in Bangladesh, supplying households with food and energy, generating income, and helping to protect the environment. This study was carried out in the hilly regions of the Rangamati district for examining farmers' perceptions of agroforestry and researching the driving forces behind the adoption of agroforestry methods and the difficulties. According to the survey results, majority of the respondents were from the Chakma community, predominantly male, in their middle age, had a secondary level of education, had a medium annual income with medium sized land, more than 20 years of average farming experience, less training and occasional cosmopolitan behavior and extension media contact. Most of the respondents showed a low level of understanding about agroforestry, they prefer cropland and fruit-based agroforestry systems with mostly planted mango trees. The most popular choice was the combination of fruit and vegetable production with tree species. Farmers also denote that they have a lack of government support which is the top-ranked problem followed by a lack of capital, inadequate training, and insufficient transport facilities. According to a correlation analysis, farmers' annual income, educational qualification, training, extension contacts, innovativeness were significantly positive with their knowledge of agroforestry systems. In conclusion, agroforestry practices could become more prevalent and adopted in this hilly region of Bangladesh with more government support on the training facilities, transport, technology, and knowledge, particularly from the Department of Agricultural Extension.